Manhunt : Unabomber : conversation avec une cabane, une boîte aux lettres et un feu tricolore - Laurence Espinosa (TV Series, 2021)
TV series can become “fields” in the anthropological sense, in a dialogue with Stanley Cavell’s philosophy. And these fields engage the subjectivity of the researcher like the other anthropological fields. So The Manhunt : Unabomber series tells Stanley Cavell in its words, its images and its sounds. The cabin, the mailbox and the tricolor fire, object - characters, say Henry David Thoreau, skepticism, ordinary language, voice or moral perfectionism. The screen brings us closer and loses us to the rhythm of the conversation that comes out.